Neuroscience in Organizational Behavior - Waldman, D.; Ward, Mary; Becker, W. (2017)
In this review, we consider the advent of neuroscience in management and organizational research.Weorganize our review around two general themes pertaining to how areas of the brain may be relevant to management and organizational behavior. First, intrinsic, at-rest activity in the brain provides trait-like information that can be used to better understand individuals in terms of cognition, emotions, and behaviors. Second, reflexive activity involves an understanding of the brain in terms of its state-like responses to stimuli. In our review, we identify several research challenges and opportunities, such as the need to consider the theoretical basis of neural concepts and measures and the use of team-based neuroscience technologies. In addition, although research in organizational neuroscience is relatively new, some interesting practical implications are raised here. We conclude with a consideration of key limitations, specifically the possibility of excessive reductionism, as well as ethical and professional issues.